PENGEMBANGAN ALAT PERAGA BANGUN RUANG TIGA DIMENSI - Siti Nurbaiti; Rahmad Bustanul Anwar; Satrio Wicaksono Sudarman (EMTEKA: Jurnal Pendidikan Matematika, 2022)
This research and development aimed to produce a learning media in the form of three-dimensional teaching aids on solid (geometry) materials that meet valid and practical criteria. This research used a 4D development model (Define, Design, Develop, Disseminate). In this study, the disseminate stage was not carried out because the purpose of this study was only to produce valid and practical products for learning. The validity of the product was shown through the assessment of the validator consisting of 2 media experts and 2 material experts, in the aspect of media validity an average percentage of 88% was included in the very valid criteria, while the material validity had an average percentage of 82% so that it was included in the very valid criteria. Thus, the validation results from the two experts obtained an average of 86% with very valid criteria. Furthermore, the results of the analysis from the practicality test stage carried out in small groups of 10 students produced an average percentage of 87% so that it was included in the very practical criteria. Based on the results obtained, it can be concluded that the three-dimensional teaching aids of solid met the valid and practical criteria.